2013
DOI: 10.1007/s10900-013-9772-z
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Screening Among Migrant/Seasonal Farmworker Women and Healthcare: A Policy Brief

Abstract: Migrant and seasonal farm working (MSFW) women report higher rates of intimate partner violence (IPV) as compared to the national average (Hazen and Soriano in Violence Against Women 13:562-582, 2007). Although prior researchers have indicated that implementing IPV screenings in healthcare settings significantly increases rates of identifying IPV (Nelson et al. in Ann Intern Med 156:1-17, 2012; Ramsay et al. in Br Med J 325:314-318, 2002); many providers opt not to screen (Jonassen and Mazor in Acad Med 78(10)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Other work has shown that farmworkers work while injured, incur musculoskeletal discomfort, have elevated depressive symptoms [Arcury et al, ], have a high prevalence of skin disease, particularly fungal disease [Krejci‐Manwaring et al, ], and sexually transmitted diseases [Scott ]. High risks of intimate partner violence has been reported among female farmworkers [Wilson et al, ] and increased morbidity [Fleischer et al, ] and mortality [Gubernot et al, ] from heat stress has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Other work has shown that farmworkers work while injured, incur musculoskeletal discomfort, have elevated depressive symptoms [Arcury et al, ], have a high prevalence of skin disease, particularly fungal disease [Krejci‐Manwaring et al, ], and sexually transmitted diseases [Scott ]. High risks of intimate partner violence has been reported among female farmworkers [Wilson et al, ] and increased morbidity [Fleischer et al, ] and mortality [Gubernot et al, ] from heat stress has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The interview guide method lists questions to be explored and is designed to ensure that each interview follows the same basic format. The probing questions were based on findings from a policy brief examining current IPV research on the MSFW population and on the principles of biopsychosocial–spiritual model . A model used to advocate that health is a biomedical, psychological, social and spiritual dimension.…”
Section: Methodsmentioning
confidence: 99%
“…According to interviewees, although sexual violence on the husband's side has decreased significantly after immigration, this issue has not ended at all. In one study, Wilson et al (2014) included "Physical violence and sexual violence/coercion as a common form of IPV before and after migration" (p. 373). Based on the comments of one interviewee, difficult economic conditions after immigration oblige men to spend long working hours outside the home which leads to reduction in the number of sexual relations and sexual violence.…”
Section: Experience Of Sexual Violencementioning
confidence: 99%